TACE versus TARE for patients with hepatocellular carcinoma: Overall and individual patient level meta analysis - Andrew M. Brown; Ihab Kassab; Marco Massani; Whitney Townsend; Amit G. Singal; Cigdem Soydal; Laura Moreno‐Luna; Lewis R. Roberts; Vincent L. Chen; Neehar D. Parikh (Cancer Medicine)
Abstract Background Transarterial radioembolization (TARE) is increasingly used as an alternative to transarterial chemoembolization (TACE) for the treatment of hepatocellular carcinoma (HCC). We aimed to perform an overall and individual patient data (IPD) meta‐analysis of studies comparing TACE and TARE. Methods We performed a systematic literature search using pre‐specified keywords with the aid of an informationist for articles from inception to 3/2020. The primary endpoint was overall survival (OS), and the secondary endpoint was time to progression (TTP). Results Seventeen studies met inclusion criteria with 2465 unique patients, with one randomized trial, 4 prospective studies and 12 retrospective studies. Barcelona Clinic Liver Cancer (BCLC) stage B (42.8%) was the most common stage followed by BCLC A (30.3%) and BCLC C (29.0%). There was no difference in OS between the two modalities (−0.55 months, 95% CI −1.95 to 3.05). In three studies with available TTP data, TARE resulted in a longer TTP than TACE (mean TTP 17.5 vs. 9.8 months; mean TTP difference 4.8 months, 95% CI 1.3–8.3 months). IPD‐level meta‐analysis of 311 patients from three studies showed no difference in overall OS between the two modalities including among subgroups stratified by tumor stage and liver function. Limitations of the current literature include inconsistent length of follow‐up, inconsistency in response criteria, and safety reporting. Conclusions Current data suggest TARE provides significantly longer TTP than TACE, although the two treatments do not significantly differ in terms of OS. Given limitations of the current data, there is rationale for prospective studies comparing these modalities.